2016
DOI: 10.1038/srep19393
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Tau Oligomers Produce An Immediate Impairment of LTP and Memory

Abstract: Non-fibrillar soluble oligomeric forms of amyloid-β peptide (oAβ) and tau proteins are likely to play a major role in Alzheimer’s disease (AD). The prevailing hypothesis on the disease etiopathogenesis is that oAβ initiates tau pathology that slowly spreads throughout the medial temporal cortex and neocortices independently of Aβ, eventually leading to memory loss. Here we show that a brief exposure to extracellular recombinant human tau oligomers (oTau), but not monomers, produces an impairment of long-term p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
209
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(226 citation statements)
references
References 67 publications
16
209
1
Order By: Relevance
“…Thus, although the existence of extracellular tau is now considered crucial for AD propagation [1, 9, 56], phospho-tau could be predominantly accumulated in the cytosol. Therefore, it is likely that most of the phospho-tau in our S1 fractions were originally located intraneuronally.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although the existence of extracellular tau is now considered crucial for AD propagation [1, 9, 56], phospho-tau could be predominantly accumulated in the cytosol. Therefore, it is likely that most of the phospho-tau in our S1 fractions were originally located intraneuronally.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we showed that several disease-related modifications of tau cause conformational display of the PAD in the amino terminus of tau and oligomeric tau aggregates impaired axonal transport confirming a link between pathological conformations and tau toxicity (Kanaan, et al, 2011,LaPointe, et al, 2009,Patterson, et al, 2011a,Patterson, et al, 2011b,Tiernan, et al, 2016). Moreover, many other studies suggest oligomeric tau is toxic to neurons in culture and in vivo (Castillo-Carranza, et al, 2014a,Castillo-Carranza, et al, 2014b,Fa, et al, 2016,Gerson, et al, 2016,Lasagna-Reeves, et al, 2010,Tian, et al, 2013,Usenovic, et al, 2015). Previous studies have focused only on the longest 4R tau isoform to study the effects of PAD exposure and oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple studies implicate oligomers as a primary toxic species of tau in several tauopathy model systems (Cardenas-Aguayo Mdel, et al, 2014,Castillo-Carranza, et al, 2014a,Fa, et al, 2016,Gerson, et al, 2016,Lewis and Dickson, 2015,Sahara, et al, 2013,Tian, et al, 2013,Usenovic, et al, 2015,Ward, et al, 2012). Here, the vast majority of aggregates produced by the 3R isoforms under the experimental conditions used were oligomeric, with only rare filaments being present in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Other proposed mechanisms for neurotoxicity include enhanced formation of degradation-resistant multimers that could overwhelm protein degradation machinery (Myeku et al, 2015; Tai et al, 2012; Wang et al, 2009) and/or compromise chaperone activity (Patterson et al, 2011a), impairment of neurophysiological functions (Fá et al, 2016), or promotion of mitochondria dysfunction (Kopeikina et al, 2011). However, the relatively low concentrations of S422E tau and the short incubation time used presently would argue against these mechanisms as an explanation for the effects on FAT.…”
Section: Discussionmentioning
confidence: 99%